LRRK2 exonic variants and susceptibility to Parkinson’s disease - Ross, Owen A. (2011)
BACKGROUND: Leucine-rich repeat kinase 2 (LRRK2) is known to harbor highly penetrant mutations linked to familial parkinsonism. However, its full polymorphic variability in relationship to Parkinson’s disease (PD) risk has not been systematically assessed. METHODS: We examined the frequency pathogenicity of 121 exonic LRRK2 variants in three ethnic series (Caucasian [N=12,590], Asian [N=2,338] and Arab-Berber [N=612]) consisting of 8,611 patients and 6,929 control subjects from 23 separate sites of the Genetic Epidemiology of Parkinson’s Disease Consortium. FINDINGS: Excluding carriers of previously known pathogenic mutations, new independent risk associations were found for polymorphic variants in Caucasian (p.M1646T, OR: 1.43, 95% CI: 1.15 – 1.78, P=0.0012) and Asian (p.A419V, OR: 2.27, 95% CI: 1.35 – 3.83, P=0.0011) populations. In addition, a protective haplotype was observed at >5% frequency (p.N551K-p.R1398H-p.K1423K) in the Caucasian and Asian series’, with a similar finding in the small Arab-Berber series that requires further study (combined 3-series OR: 0.82, 95% CI: 0.72 – 0.94, P=0.0043). Of the two previously reported Asian risk variants p.G2385R was found to be associated with disease (OR: 1.73, 95% CI: 1.20 – 2.49, P=0.0026) but no association was observed for p.R1628P (OR: 0.62, 95% CI: 0.36 – 1.07, P=0.087). Also in the Arab-Berber series, p.Y2189C showed potential evidence of risk association with PD (OR: 4.48, 95% CI: 1.33 – 15.09, P=0.012). Of note, two variants (p.I1371V and p.T2356I) which have been previously proposed as pathogenic were observed in patient and control subjects at the same frequency. INTERPRETATION: LRRK2 offers an example where multiple rare and common genetic variants in the same gene have independent effects on disease risk. Lrrk2, and the pathway in which it functions, is important in the etiology and pathogenesis of a greater proportion of patients with PD than previously believed. FUNDING: The present study and original funding for the GEO-PD Consortium was supported by grants from Michael J. Fox Foundation. Studies at individual sites were supported by a number of funding agencies world-wide.